The Effect of Capital Structure and Liquidity on Earnings Growth with Dividend Policy as A Moderating Variable - Aqila, Alfiana (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to analyze the effect of capital structure and liquidity on profit growth with dividend policy as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange for the 2021–2023 period. This research uses a quantitative approach. The type of data used is secondary data in the form of audited annual financial statements. The sampling technique used is purposive sampling based on certain criteria, resulting in 38 companies as the sample with a research period of 3 years, so the total sample used in this study is 114. The data analysis technique used is Moderated Regression Analysis (MRA) with the assistance of SPSS software. The results of the study indicate that capital structure has a negative effect on profit growth, while liquidity does not affect profit growth. In addition, dividend policy moderates the effect of capital structure on profit growth. However, dividend policy does not moderate the effect of liquidity on profit growth.